Music Performance Hall in Kendari City with Modern Architectural Approach - Sari, Novita Kumala; Nahdatunnisa, Nahdatunnisa; Taufiq, Elvina Sari (PT FORMOSA CENDEKIA GLOBAL, 2024)
The music performance hall is a multifunctional facility designed to present various types of musical performances. The architectural structure not only pays attention to aesthetic aspects, but also optimal acoustic functionality. The choice of materials and space design was carried out carefully to minimize sound interference and ensure clear sound quality throughout the auditorium. In modern design, music performance halls often adopt flexible architectural elements, allowing for adjustments to the layout for different types of events, from large-scale performances to intimate performances with a limited audience. Apart from that, supporting facilities such as artist dressing rooms and spacious rehearsal rooms are very important to support the smooth running of the performance. State-of-the-art lighting and stage technology are also an integral part of the design, providing an immersive visual experience for the audience. With a combination of aesthetic architecture, state-of-the-art sound technology and complete facilities, the music performance hall acts as a strategic place to support the development of musical arts and provide an immersive experience for every visitor.